Anisotropic Seismic Wave Simulation via Pseudo-spectral and Pseudo-acoustic Approximations - Y. Moussavi Alashloo, S.; Ghosh, Deva; Abbas Babasafari, Amir; Bashir, Yasir (International Journal of Engineering and Technology, 2018)
Nowadays, the concept of seismic anisotropy is applied widely in seismic modelling, imaging and inversion. To appreciate the influences of seismic anisotropy, an anisotropic wave equation needs to be employed. Despite the fact that seismic anisotropy is innately an elastic phenomenon, the elastic anisotropic wave equation rarely employed in imaging methods because of its time-consuming computational operation. Pseudo-acoustic equations are proposed to reduce the computational cost, even though, they have a few drawbacks. Pseudo spectral approaches are appropriate alternatives for pseudo acoustic methods. In this paper, we aim to study different techniques applied to propagate seismic wave in anisotropic environment. Firstly, the theory and results of a pseudo acoustic wave propagator are demonstrated. Then, a spectral technique based on lowrank approximation for modelling pure acoustic waves is discussed, and we investigate and compare its accuracy and efficiency to the pseudo acoustic method.Â Â